Direct Mechanical Stimulation of Stem Cells: A Beating Electromechanically Active Scaffold for Cardiac Tissue Engineering. Issue 12 (29th April 2016) - Gelmi, Amy; Cieslar‐Pobuda, Artur; de Muinck, Ebo; Los, Marek; Rafat, Mehrdad; Jager, Edwin W. H.
Abstract : The combination of stem cell therapy with a supportive scaffold is a promising approach to improving cardiac tissue engineering. Stem cell therapy can be used to repair nonfunctioning heart tissue and achieve myocardial regeneration, and scaffold materials can be utilized in order to successfully deliver and support stem cells in vivo. Current research describes passive scaffold materials; here an electroactive scaffold that provides electrical, mechanical, and topographical cues to induced human pluripotent stem cells (iPS) is presented. The poly(lactic‐ co ‐glycolic acid) fiber scaffold coated with conductive polymer polypyrrole (PPy) is capable of delivering direct electrical and mechanical stimulation to the iPS. The electroactive scaffolds demonstrate no cytotoxic effects on the iPS as well as an increased expression of cardiac markers for both stimulated and unstimulated protocols. This study demonstrates the first application of PPy as a supportive electroactive material for iPS and the first development of a fiber scaffold capable of dynamic mechanical actuation. Abstract : Here a new type of smart cardiac patch material, the electromechanically active fiber scaffold, is presented. The scaffold is capable of delivering electrical and mechanical stimulation to individual cells and demonstrates controlled volume change actuation. The scaffold is noncytotoxic and may enhance the cardiac differentiation of human induced pluripotent stem cells.